THE EXISTENCE OF PEER ACCEPTANCE FOR STRENGTHENING STUDENTS' SOCIAL SKILLS - Ai Sukmaningsih; Tetep (Institut Pendidikan Indonesia, 2021)
Developing social skills is an important thing for students to have because it can form awareness of behavior for students, both in terms of interacting with other people, how to communicate, building a group that strengthens each other, trusts each other and to the extent that individuals are able to solve problems. The purpose of conducting this research is (1) to determine the understanding of peer acceptance of students at SMPN 1 Pakenjeng. (2) knowing the social skills of students at SMPN 1 Pakenjeng. (3) find out how effective peer acceptance is in strengthening the social skills of students at SMPN 1 Pakenjeng. The background to this research is the low level of peer acceptance, which has an impact on strengthening students' social skills. This research uses a quantitative approach, collecting data through distributing questionnaires and interviews. The population was all class VII students at SMPN 1 Pakenjeng, then through simple random sampling finally obtained 35 students as respondents. Based on the results of the research, it shows that (1) the understanding of peer acceptance among SMPN 1 Pakenjeng students is classified as sufficient/medium (2) the form of social skills in SMPN 1 Pakenjeng students is Self-related Behavior (behavior related to oneself) (3) the existence of acceptance Peers are quite effective in strengthening social skills in students at SMPN 1 Pakenjeng.